The role of Ismail Gasprinsky in the light of archaeological research works in the Khan`s Dere valley - Selvina Seitmemetova; Shukri Seytumerov (Крымское историческое обозрение, 2020)
The article examines the course of excavations made by the Taurida Scientific Archival Commission in the Khan`s Dere valley. It was given in the coverage of the newspaper “Terdzhiman” through the prism of the views of its editor – Ismail Gasprinsky, who witnessed the discovery of previously unknown Muslim monuments. The materials about the other periodicals, issued at the end of the XIX century, concerning the newly discovered mausoleums in the Khan`s Dere valley, versions concerning their origin and Dating, were also considered in the article.